Human Retinal Progenitor Cells Derived Small Extracellular Vesicles Delay Retinal Degeneration: A Paradigm for Cell-free Therapy - Chen, Min; Ren, Chunge; Ren, Bangqi; Fang, Yajie; Li, Qiyou; Zeng, Yuxiao; Li, Yijian; Chen, Fang; Bian, Baishijiao; Liu, Yong (Frontiers in Pharmacology, 2021)
Retinal degeneration (RD) is a leading cause of irreversible vision impairment and blindness worldwide. Previous studies indicate that subretinal injection of human retinal progenitor cells (hRPCs) can delay the progression of retinal degeneration, preserve retinal function, and protect photoreceptor cells from death, albeit the mechanism is not well understood. In this study, small extracellular vesicles derived hRPCs (hRPC-sEVs) were injected into the subretinal space of retinal dystrophic RCS rats. We find that hRPC-sEVs significantly preserve the function of retina and thickness of the ONL, reduce the apoptosis of photoreceptors in the ONL, and suppress the inflammatory response in the retina of RCS rats. In vitro, we have shown that hRPC-sEVs treatment could significantly reserve the low glucose preconditioned apoptosis of photoreceptors, and reduce the expression of pro-inflammatory cytokines in microglia. Pathway analysis predicted the target genes of hRPC-sEVs miRNAs involved in inflammation related biological processes and significantly enriched in processes autophagy, signal release, regulation of neuron death, and cell cycle. Collectively, our study suggests that hRPC-sEVs might be a favorable agent to delay retinal degeneration and highlights as a new paradigm for cell-free therapy.